O lance é recordar: os usos dos testemunhos de torcedores na construção das memórias e identidades de times de futebol nos documentários da G7 Cinema - Medeiros, Julian Andrey Muniz de (2024)
This work puts into play the memories and identities of football times in cinema, with the characteristic of the culture of memory as the background flag. From 1980 onwards, memories will gain more and more fields (WINTER, 2006) as elements of the past will be increasingly present in Western society, what Huyssen (2000) called the culture of memory. On the football and cinema pitches it is possible to observe the public looking at the production company G7 Cinema. The company sold 10 documentaries about past football experiences. Given the opening whistle, we seek to answer the following research problem: how do the uses of fans' testimonies contribute to the construction of memories and identities of football times in G7 Cinema's documentaries? In the work, we train the concepts of memory based on Jan Assmann (2016), Aleida Assmann (2011) and Joël Candau (2021) playing with the concept of identity under the eyes of Stuart Hall (2006, 2009) and Manuel Castells (1999). We also discuss documentary as a memory medium based on Aleida Assmann (2011) and Cássio Tomaim (2016). As a methodological procedure, we carried out the following research movements: exploratory, bibliographic, documentary and film analysis. When playing the game we can point out as a result, that in the films Fiel – O Filme (2009), Soberano - Seis Vezes São Paulo (2010) and Supremacia Vermelha – 100 anos de Grenal (2010) the uses of fans' testimonies, in the dimensions of art direction, photography direction and editing accentuate symbolic elements of club membership. As fan recordings become communicative memories, supported and preserved in memory media, as in the documentaries analyzed here, scripted with the aim of connecting feelings and vivid experiences around historical moments of football clubs, we can state that These audiovisual productions seek in the affective memories of fans elements that intertwine individual memories and collective memories in the sense of transmitting a culture of football clubs around a commemorative past.